Hand fasciae innervation: The palmar aponeurosis. Issue 5 (14th April 2018) - Stecco, Carla; Macchi, Veronica; Barbieri, Alessandro; Tiengo, Cesare; Porzionato, Andrea; De Caro, Raffaele
Abstract : There are few data in the scientific literature about the innervation of fasciae of the hand. The present study first elucidates the density and location of nervous structures in the palmar aponeurosis and, for comparison, in the flexor retinaculum (both can be considered specializations of the deep fascia of the upper limbs). Second, it compares nonpathological with pathological palmar aponeurosis. Samples of nonpathological fascia were taken from the flexor retinaculum and palmar aponeurosis of 16 upper limbs of unembalmed cadavers. Samples of pathological palmar aponeurosis were taken from seven patients with Dupuytren's disease. All samples were stained immunohistochemically with anti‐S100 and anti‐tubulin antibodies, and analyzed quantitatively and qualitatively by microscopy. The palmar aponeurosis showed higher median density than the retinacula of free nerve endings (22 and 20 elements/cm 2, respectively), Pacinian corpuscles (2 and 0 elements/cm 2 ) and Golgi‐Mazzoni corpuscles (1.0 and 0.5 element/cm 2 ). Some corpuscles were located at the intersections of the fibers in the three directions. Free nerve endings were denser in pathological palmar aponeurosis (38 elements/cm 2 ). The results indicate that the palmar aponeurosis is central to proprioception of the hand and that surgery should therefore avoid injuring it. The higher density of free nerve endings in pathological samples indicates that the nervous structures are implicated in the amplified fibrosis of Dupuytren's disease. Clin. Anat. 31:677–683, 2018. © 2018 Wiley Periodicals, Inc.